2006
DOI: 10.1093/pasj/58.4.l23
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Dwarf Nova, TSS J022216.4+412259.9: WZ Sge-Type Dwarf Nova Breaking the Shortest Superhump Period Record

Abstract: We report on the time-resolved CCD photometry of a newly discovered variable star, TSS J022216.4+412259.9 during the outburst in 2005 November-December brightening. The obtained light curves unambiguously showed 0.2-0.3 mag modulations, which we confirmed to be the superhump observed among SU UMa-type dwarf novae. We also performed a period search for the data obtained during the outburst plateau phase, and revealed the existence of the two periodicities: 0.054868(98) days for the first two nights and 0.055544… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…The origin of unique light variations, as well as their evolutionary status, are still in debate (e.g., Osaki, Meyer 2003;Nakata et al 2014; see Kato 2015 for a review). Their observational properties are that (1) the amplitude of the superoutburst is large, exceeding ∼ 6 mag (Howell et al 1995), (2) the interval between the successive superoutbursts (supercycle) is unusually long, typically with a time scale of decades (Kato et al 2001), (3) modulations with double-peaked profiles called early superhumps are observed in the early phase of the superoutburst (Kato 2002), and (4) after the end of the plateau stage, single or multiple rebrightenings are observed (Imada et al 2006). Among them, properties (3) and (4) are considered to be unique to WZ Sge-type dwarf novae and to be the defining characteristics (see Kato 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of unique light variations, as well as their evolutionary status, are still in debate (e.g., Osaki, Meyer 2003;Nakata et al 2014; see Kato 2015 for a review). Their observational properties are that (1) the amplitude of the superoutburst is large, exceeding ∼ 6 mag (Howell et al 1995), (2) the interval between the successive superoutbursts (supercycle) is unusually long, typically with a time scale of decades (Kato et al 2001), (3) modulations with double-peaked profiles called early superhumps are observed in the early phase of the superoutburst (Kato 2002), and (4) after the end of the plateau stage, single or multiple rebrightenings are observed (Imada et al 2006). Among them, properties (3) and (4) are considered to be unique to WZ Sge-type dwarf novae and to be the defining characteristics (see Kato 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hiroi et al (2009), this difference can be understood as the presence of the mass reservoir, which are the outer gas of the accretion disk and will result in the mass donor for rebrightenings (Kato et al 1998). As V455 And also did not show any rebrightenings along with GW Lib (Type-D rebrightening; Kato et al 2009;Imada et al 2006), this interpretation still holds among V455 And, GW Lib and WZ Sge.…”
Section: The Time Evolution Of Spectramentioning
confidence: 91%
“…Rebrightenings or echo outbursts are one of most striking characteristics of WZ Sge objects. Imada et al (2006) suggested to classify all detected rebrightenings in following 4 types:…”
Section: Phenomenon Of Rebrighteningsmentioning
confidence: 99%